An Analysis of Ice-Breaking Questions Technique on Students’ Participation in Speaking Activities - Mei Rohamah; Nafisah Endahati (Globish: An English-Indonesian Journal for English, Education, and Culture, 2026)
This study analyzed the use of ice-breaking questions as a technique to improve students' participation in English speaking activities. Many students in EFL classrooms remained passive during speaking sessions due to anxiety, low confidence, and lack of motivation. The research aimed to describe how the teacher implemented the technique and to explore students’ perceptions of its influence on their participation in speaking activities. A qualitative case study approach was used, involving 5 students from grade X Dance 4 at SMK Negeri 1 Kasihan. Data were collected through classroom observations, field notes, interviews, and documentation, then analyzed using thematic analysis. The findings showed that the teacher regularly used various types of ice-breaking questions, including WH-questions and funny questions, before starting the lesson. Students stated that the technique made them feel more relaxed, confident, and motivated to speak. The use of ice-breaking questions successfully created a positive classroom atmosphere that supported student interaction and active speaking participation.